Animal performance, carcass characteristics and beef fatty acid profile of grazing steers supplemented with corn grain and increasing amounts of flaxseed at two animal weights during finishing - Pouzo, Laura Beatriz; Fanego, Noelia; Santini, Francisco Jose; Descalzo, Adriana Maria; Pavan, Enrique (Elsevier, 2018)
The objective of this study was to determine (1) the effects of increasing flaxseed addition to the corn grain supplemented at finishing to grazing steers on animal performance, carcass characteristics and longissimus muscle (LM) fatty acid profile, and (2) whether dietary treatments effects are affected by animal body weight (BW) at supplementation. Forty eight steers were assigned to eight treatment combinations defined by four dietary treatments (CNTRL, no supplement; FLAX-0, 0.7% BW of cracked corn grain; FLAX-1 and FLAX-2, FLAX-0 plus 0.125% and 0.250% BW of unprocessed flaxseed, respectively) and by two animal BW treatments generated by supplementing steer in early spring (EARLY) or late spring (LATE). Steers assigned to EARLY received their dietary treatment when reaching 366±27.3 kg BW (August, 3rd) and those assigned to LATE when reaching 458±42.8 kg (October, 10th). After 70 d on trial, carcass data and LM samples (12th rib region) were collected for fatty acid (FA) analysis. Total DMI was greater in supplemented treatments (FLAX-0, FLAX-1 and FLAX-2) than in CNTRL, with no flaxseed level effect. Dietary treatment effects on performance and carcass characteristics were not affected by BW treatments. Increasing flaxseed supplementation linearly increased subcutaneous fat thickness; whereas increasing BW at initiation of supplementation decreased average daily again, but increase final BW, hot carcass weight, and LM total fatty acid content. Animal BW at initiation of supplementation affected dietary treatments effects on LM n-6/n-3 ratio; ratio was highest in FLAX-0 and lowest in CNTRL and FLAX-2 in both BW treatments; did not differ between BW treatments in CNTRL and in FLAX-2, but was greater in EARLY than in LATE in FLAX-0 and FLAX-1. Trans-vaccenic acid proportion was greater in CNTRL than in supplemented treatments, but was not affected by flaxseed level; similar trend was observed for CLA cis-9, trans-11 proportion. Linolenic acid proportion did not differ between CNTRL and supplemented treatments, but was linearly increased with flaxseed level. Fatty acids changes with increasing animal BW at supplementation were associated with the increased in total muscle fatty acid content; total and individual polyunsaturated fatty acids were lower in LATE than in EARLY, whereas trans-vaccenic acid and CLA cis-9, trans-11 were greater. Adding flaxseed to the corn grain supplemented increase subcutaneous fat thickness of grazing steers without negatively affecting fatty acid profile, except for a reduction in trans-vaccenic acid proportion. Therefore, adding flaxseed to the corn supplemented to grazing steers increases carcass fatness while reducing the negative effect of corn supplementation on LM n-6/n-3 ratio but not on trans-vaccenic acid. Increasing BW at supplementation reduces supplementation effects on LM n-6/n-3 ratio.